Activity-Based Teaching, Student Motivation and Academic Achievement (Journal of Education and Educational Development, 2020)
This research was conducted to determine the effects of activity-based teaching on student motivation and academic achievement. Pretest and post-test control group design of experimental research was employed for this study. Two MCQ achievement tests were used as research tools for the data collection as pre-test and post-test. The first step in this project was to gather information about what motivates students to learn. Pre-test was conducted from both groups and results were tabulated. The second step of the project was to examine the effect of hands-on activities on student motivation and for analysis MCQ achievement test was used along with specially designed work sheets from both groups. T-test was used to analyze the data. The results of this study showed that a majority of students’ scores increased in experimental group as compared to the control group. The mean value indicated that participants from experimental group showed more achievement in post-test 15.6, while the control group students scored 10.7. The post-lesson survey showed that the majority students found the activity based teaching to be more interesting than lecture based teaching.